L’analyse stratégique et quelques développements récents en criminologie - Cusson, Maurice (Criminologie, 1986)
Strategic analysis views crime as a confrontation and as a mean to an end. It is characterised by : 1) it concentrates on crime; 2) it takes cognizance of the circumstances under which the crime is committed; 3) it presents the crime as a decision influenced by its anticipated results. Felson's routine activity approach, which is similar to strategic analysis, is presented in this article. Other recent developments in criminology have made it possible to present several assertions with a view to explaining certain aspects of theft, in particular, the choice of target. These assertions are : 1) thefts vary according to the opportunities offered potential thieves; 2) opportunity is defined as the contact between a potential criminal and a suitable target; 3) the number of contacts between potential criminals and suitable targets varies directly with the number of targets and their accessibility; 4) the suitability of targets varies in direct proportion to their value and vulnerability. It varies in inverse proportion to their inertia.